Sulfated polysaccharides from Enteromorpha prolifera suppress SREBP-2 and HMG-CoA reductase expression and attenuate non-alcoholic fatty liver disease induced by a high-fat diet. Issue 5 (21st April 2017) - Ren, Rendong; Gong, Junjie; Zhao, Yanyan; Zhuang, Xinyun; Ye, Yin; Lin, Wenting
Abstract : Enteromorpha prolifera polysaccharides (EP) suppressed SREBP-2 and regulates expression of HMG-CoA reductase. Therefore, EP may be a functional food that can prevent nonalcoholic fatty liver disease. Abstract : Non-alcoholic fatty liver disease (NAFLD) is caused by fat accumulation and is associated with abnormal cholesterol metabolism. Previous work indicates that polysaccharides from alga Enteromorpha prolifera improve glucose metabolism and lower cholesterol in diabetic rats. Thus, we studied the possible protective effects of E. prolifera polysaccharides (EP) in the development of NAFLD and underlying mechanisms. EP (200 mg kg −1 ) significantly reduced the liver weight and significantly lowered hepatic HMG-CoA reductase (HMGCR) mRNA protein expression. EP suppressed sterol regulatory element binding protein-2, which is a key transcription factor in cholesterol metabolism and regulates the expression of HMGCR. Therefore, EP may be a functional food that can prevent NAFLD.